PENERAPAN TEKNIK ROLE PLAY UNTUK MENINGKATKAN SOCIAL SKILLS ACQUISITION (AKUISISI KETERAMPILAN SOSIAL) PADA REMAJA - Fitriana, Riza (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2023)
As social creatures, each individual is required to be able to make adjustments in the social environment. But in fact, there are individuals who have difficulty making adjustments because they have a social skills deficit. Social skills deficits can be measured using the Social Skills Rating System (SSRS) which refers to the theory of Gresham and Elliott which explains that there are five aspects that can be used as a reference for measuring social skills, namely empathy, assertive behavior, self-control, cooperation, and responsibility. Based on these conditions, the researcher conducted an experimental study to determine the effectiveness of the Role Play Technique as an effort to overcome the social skills deficit that individuals have. This study involved a 16-year-old female adolescent who was studying at a Vocational High School. Based on the results of the SSRS measurement, the teenager experienced a social skills deficit. The method used in this study is a single case experimental design (DEKT), with pre-test and post-test given to the subject, teacher, and subject's parents. The result is that the Role Play Technique is able to improve the subject's social skills acquisition. The improvement includes the five aspects of social skills, namely the subject has shown assertive, cooperative, responsible, self-controlled, and empathetic behaviors. Overall, the subject's social skills after intervention with the Role Play Technique were in the high category.